The validity and inter-device variability of the Apple Watch™ for measuring maximal heart rate. Issue 13 (3rd July 2018) - Abt, Grant; Bray, James; Benson, Amanda Clare
ABSTRACT: Maximal heart rate (HRmax ) is a fundamental measure used in exercise prescription. The Apple Watch™ measures heart rate yet the validity and inter-device variability of the device for measuring HRmax are unknown. Fifteen participants completed a maximal oxygen uptake test while wearing an Apple Watch™ on each wrist. Criterion HRmax was measured using a Polar T31™ chest strap. There were good to very good correlations between the watches and criterion (left: r = 0.87 [90%CI: 0.67 to 0.95]; right: r = 0.98 [90%CI: 0.94 to 0.99]). Standardised mean bias for the left and right watches compared to the criterion were 0.14 (90%CI: −0.12 to 0.39; trivial) and 0.04 (90%CI: −0.07 to 0.15; trivial). Standardised typical error of the estimate for the left and right watches compared to the criterion were 0.51 (90%CI: 0.38 to 0.80; moderate) and 0.22 (90%CI: 0.16 to 0.34; small). Inter-device standardised typical error was 0.46 (90%CI: 0.36 to 0.68; moderate), ICC = 0.84 (90%CI: 0.65 to 0.93). The Apple Watch™ has good to very good criterion validity for measuring HRmax, with no substantial under- or over-estimation. There were moderate and small prediction errors for the left and right watches. Inter-device variability in HRmax is moderate.